Evaluasi Program Perumahan Swadaya di Kabupaten Boyolali - Utari Ardiyanti; Widjonarko Widjonarko (Teknik PWK (Perencanaan Wilayah Kota), 2016)
The number of uninhabitable housing is one of the main issues in Indonesia. Approximately 13.5 million backlog in Indonesia in which 3.4 million units are uninhabitable houses (Ministry of PUPR, 2015). In an effort to accelerate the realization of the ideals of society so that each family occupying the house livable in healthy neighborhoods with community involvement, it is necessary to the development of self-supporting housing. Starting from the concept of self-supporting housing idea as an alternative for the provision of housing development for low-income people in Boyolali, it needs to be replicated on the effectiveness of the implementation of self- supporting housing program in the field whether it is still appropriate as an alternative towards providing housing to community empowerment. This study aims to determine the success and effectiveness of the implementation of self-supporting housing program in Boyolali.The method used in this research is quantitative. Data collection techniques using observation, questionnaires with sampling technique is purposive sampling and using secondary data. The analysis used is descriptive analysis.Based on the research that has been done that the implementation of self-supporting housing program in Boyolali less successful in establishing appropriate housing, with the implementation of the program is less effective because the average percentage yield 45.63%. Such conditions can be seen from the aspect: Inaccuracy time reduction in funds, the recipient experienced a shortage of funds, lack of understanding by the recipient, the village chief task mismatch, no socialization and proposals by the community and less on target. Self- supporting housing program for the benefit of beneficiaries, in terms of health has been able to reduce the number of diseases associated with home is not livable. But in economic terms have not been able to significantly increase incomes